Metode Estimasi Massa Karbon Pohon Jeunjing (Paraserianthes falcataria L Nielsen) di Hutan Rakyat (Method for Estimation of Tree Carbon Mass of Paraserianthes falcataria L Nielsen in Community Forest) - Elias .; I Nyoman Jaya Wistara (Jurnal Manajemen Hutan Tropika, 2009)
The study was conducted at Jalagajaya Village, Jasinga Subdistrict, Bogor District, West Java, Indonesia. The objective of the study was to apply a methodology and method for tree carbon mass stock estimation in community forest based on a field survey of the forest and a model of tree carbon mass equation. The study revealed that there was a difference on carbon content in the parts of the tree biomass. Based on the analysis, model of tree carbon mass equation of Paraserianthes falcataria L Nielsen at Julagajaya Village was C = 0.7D1.48, with R² adj. = 95.7%. Results of the tree carbon mass estimation of the Paraserianthes falcataria L Nielsen based on the tree carbon mass-equation model were lower than the results estimated based on the tree biomass-equation model of Brown (1997), but higher than the results estimated based on the tree biomass-equation model of Ketterings et al. (2001). The study showed that the tree carbon stock of the community forest Paraserianthes falcataria L Nielsen at Julagajaya Village in 1,2,3,4,5, and 6 year age stand were 29.262, 33.555, 36.041, 39.163, 33.163, and 56.943 ton ha-1, respectively.Keywords: biomass-equation model, tree carbon mass-equation model, tree carbon stock, communityforest